Vibration Excitation Analysis of Transmission Error and Tooth Modification Design of Spur Gear - Liu Hongqi; Zhang Jingcai; Zhao Xiangfei; Yang Chao (Jixie chuandong)
Based on the study of relation of mesh deflection of spur gear,three key elements of tooth modification,transmission error and its frequency spectrum,the three principles of tooth modification design are defined for good transmission to get lower vibration excitation. And the modification optimizing and design method are analyzed for heavy load,light load and for both load cases.